Reclassifying severity after 48 hours could better predict mortality in acute respiratory distress syndrome. (July 2020) - Chiu, Li-Chung; Lin, Shih-Wei; Liu, Pi-Hua; Chuang, Li-Pang; Chang, Chih-Hao; Hung, Chen-Yiu; Li, Shih-Hong; Lee, Chung-Shu; Wu, Huang-Pin; Huang, Chung-Chi; Li, Hsin-Hsien; Kao, Kuo-Chin; et al.
Background: Disease severity may change in the first week after acute respiratory distress syndrome (ARDS) onset. The aim of this study was to evaluate whether the reclassification of disease severity after 48 h (i.e. day 3) of ARDS onset could help in predicting mortality and determine factors associated with ARDS persistence and mortality. Methods: We performed a secondary analysis of a 3-year prospective, observational cohort study of ARDS in a tertiary care referral center. Disease severity was reclassified after 48 h of enrollment, and cases that still fulfilled the Berlin criteria were regarded as nonresolving ARDS. Results: A total of 1034 ARDS patients were analyzed. Overall hospital mortality was 57.7% (56.7%, 57.5%, and 58.6% for patients with initial mild, moderate, and severe ARDS, respectively, p  = 0.189). On day 3 reclassification, the hospital mortality rates were as follows: resolved (42.1%), mild (47.9%), moderate (62.4%), and severe ARDS (76.1%) ( p  < 0.001). Patients with improving severity on day 3 had lower mortality (48.8%), whereas patients with the same or worsening severity on day 3 had higher mortality (62.7% and 76.3%, respectively). Patients who were older, had lower PaO2 /FiO2, or higher positive end-expiratory pressure on day 1 were significantly associated with nonresolving ARDS on day 3. A Cox regression model with ARDS severity as a time-dependent covariate and competing risk analysis demonstrated that ARDS severity was independently associated with hospital mortality, and nonresolving ARDS had significantly increased hazard of death than resolved ARDS ( p  < 0.0001). Cumulative mortality curve for ARDS severity comparisons demonstrated significantly different (overall comparison, p  < 0.001). Conclusions: Reclassification of disease severity after 48 h of ARDS onset could help to divide patients into subgroups with greater separation in terms of mortality. The reviews of this paper are available via the supplemental material section.